Learning and Teaching Measurment Year Book 2003 - Clements, Douglas H.; Bright, George H. (Reston, VA National Council of Teachers of Mathematics, 2003)
Measurement can develop in the earliest years from children's experience, and it readily lends itself to real-world application.
Focusing on research and practice, NCTM's 2003 Yearbook presents current thinking about the learning and teaching of measurement, including students' understanding, the mathematics of measurement, estimation and approximation, connections, and pedagogy.
The companion booklet, which not only illustrates some of the issues from the yearbook but also contains activities that go beyond the content, contains teaching notes and ready-to-use handouts.
Contents Preface. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . xi DOUGLAS H. CLEMENTS University at Buffalo, State University of New York Buffalo, New York Part 1: Elementary School Introduction . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 MICHELLE STEPHAN Purdue University Calumet Hammond, Indiana JOANNE MENDIOLA Herman Badillo Bilingual Academy 76 Buffalo, New York 1. Linear, Area, and Time Measurement in Prekindergarten to . . . . . . . . 3 Grade 2 MICHELLE STEPHAN Purdue University Calumet Hammond, Indiana DOUGLAS H. CLEMENTS University at Buffalo, State University of New York Buffalo, New York 2. Understanding Children’s Developing Strategies and Concepts for Length . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 17 JEFFREY E. BARRETT Illinois State University Normal, Illinois GRAHAM JONES Illinois State University Normal, Illinois CAROL THORNTON Illinois State University Normal, Illinois SANDRA DICKSON Parkside Elementary School Normal, Illinois vi CONTENTS 3. Making Connections with Powerful Ideas in the Measurement of Length . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 31 NICOLA YELLAND RMIT University Bundoora, Victoria, Australia 4. Developing the Building Blocks of Measurement with Young Children . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 46 THERESA J. GRANT Western Michigan University Kalamazoo, Michigan KATE KLINE Western Michigan University Kalamazoo, Michigan 5. Benchmarks as Tools for Developing Measurement Sense . . . . . . . . . 57 ELANA JORAM University of Northern Iowa Cedar Falls, Iowa 6. Assessing and Developing Measurement with Young Children . . . . . 68 DOUG CLARKE Australian Catholic University Melbourne, Victoria, Australia JILL CHEESEMAN Australian Catholic University Melbourne, Victoria, Australia ANDREA MCDONOUGH Australian Catholic University Melbourne, Victoria, Australia BARBARA CLARK Monash University Melbourne, Victoria, Australia 7. Count Me into Measurement: A Program for the Early Elementary School. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 81 LYNNE OUTHRED Macquarie University Sydney, New South Wales, Australia MICHAEL MITCHELMORE Australian Centre for Educational Studies Sydney, New South Wales, Australia DIANE MCPHAIL Department of Education and Training Ryde, New South Wales, Australia PETER GOULD Department of Education and Training Ryde, New South Wales, Australia vii CONTENTS 8. Developing an Understanding of Measurement in the Elementary Grades . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 100 RICHARD LEHRER University of Wisconsin—Madison Madison, Wisconsin LINDA JASLOW Ed and Verma Pastor Elementary School Phoenix, Arizona CARMEN L. CURTIS Country View Elementary School Verona, Wisconsin 9. Understanding Students’ Thinking about Area and Volume Measurement . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 122 MICHAEL T. BATTISTA Kent State University Kent, Ohio 10. Structuring a Rectangle: Teachers Write to Learn about Their Students’ Thinking . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 143 DEBORAH SCHIFTER Educational Development Center Newton, Massachusetts JANICE SZYMASZEK Smith College Campus School Northampton, Massachusetts 11. About Students’ Understanding and Learning the Concept of Surface Area . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 157 CINZIA BONOTTO University of Padua Padua, Italy 12. The Measurement of Time: Transitivity, Unit Iteration, and Conservation of Speed . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 169 CONSTANCE K. KAMII University of Alabama—Birmingham Birmingham, Alabama KATHY LONG University of California at Berkeley Berkeley, California 13. Bridging Yup’ik Ways of Measuring to Western Mathematics . . . . . 181 JERRY LIPKA University of Alaska Fairbanks Fairbanks, Alaska TOD SHOCKEY Mesa State College Grand Junction, Colorado BARBARA ADAMS University of Alaska Fairbanks Fairbanks, Alaska Part 2: Secondary School Introduction . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 195 VERONICA MEEKS Western Hills High School Fort Worth, Texas ROBERT F. WHEELER Northern Illinois University DeKalb, Illinois 14. What Students Know about Measurement: Perspectives from the NAEP. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 197 MARILYN E. STRUTCHENS Auburn University Auburn, Alabama W. GARY MARTIN Auburn University Auburn, Alabama PATRICIA ANN KENNEY University of Michigan—Ann Arbor Ann Arbor, Michigan 15. Providing Opportunities for Students and Teachers to “Measure Up”. . . . .
Hard cover
Keywords: Mathematics - Study and teaching